Using Diatom Indices to Evaluate Water quality In Abu-Zirig Marsh Thi-Qar Province /south of Iraq (Baghdad Science Journal, 2020)
The study attempts to assess water quality in Abu-Zirig Marsh which used epiphytic Diatom community for assessing water quality. Many of Diatom indices {Trophic diatom index (TDI), Diatom index (DI), Generic diatom index (GDI) have been used to give qualitative information about the status of the freshwater ecosystem(good, moderate, high pollution). In this study, the epiphytic diatoms on both host aquatic plants Phragmites australis and Typha domengensis were collected from Abu-Zirig Marsh within Thi-Qar Province at three sites in Autumn, 2018 and winter, 2019. Epiphytic diatoms were Identified by the preparation of permanent slides method, some species of epiphytic diatom showed dominance such as Cyclotella meneghiniana, Gomphonema angustatum, Cocconies placentula, Cymbella affinis, Navicula cryptoephala, Nitzschia linearis, N. dissipata, Surirella ovalis. Abundant diatoms indicated trophic conditions of the Marsh. The results of diatom indices revealed that IPS (10-12.5) is a moderate pollution condition of marsh, DI (2.9-3.4) range from high to moderate pollution condition, TDI (47.2-60.8) indicates trophic condition ranging from (oligo-mesotrophic to eutrophic) condition of marsh while GDI a range between (11.6-13.7) moderate pollution condition, the aim of the study that is about evaluating water quality of Abu-Zirig Marsh by using Diatom indices (IPS,DI,TDI and GDI), as well as due to scarce local previous studies of epiphytic diatoms and used as bio-indicator of water quality in Abu-Zirig Marsh, therefor suggested this study .